Serum interleukin-6 in the diagnosis of bacterial infection in cirrhotic patients: A meta-analysis. Issue 41 (October 2016) - Wu, Yinlian; Wang, Mingfang; Zhu, Yueyong; Lin, Su
Abstract: Background: The diagnostic accuracy of interleukin-6 (IL-6) in predicting bacterial infection in cirrhotic patients remains unclear. The aim of this meta-analysis is to explore the potential diagnostic value of IL-6 in cirrhotic patients. Methods: We systematically searched PubMed, Embase (via OvidSP), Web of Science, the Cochrane Library, and Scopus for studies published from inception to October 2015. Studies were enrolled if they included assessment of the accuracy of IL-6 in the diagnosis of bacterial infection in cirrhotic patients and provided sufficient data to construct a 2 × 2 contingency table. Results: Totally, 535 studies were searched in the initial database and finally 6 studies involving 741 patients were included for the final analysis. The pooled sensitivity, specificity and diagnostic odds ratio were 0.85 (95% confidence interval [CI], 0.64–0.94), 0.91 (95% CI, 0.80–0.96) and 52.89 (95% CI, 15.21–183.86), respectively. The pooled positive likelihood ratio was 8.99 (95% CI, 4.13–19.55) and the pooled negative likelihood ratio was 0.17 (95% CI, 0.07–0.43). The area under the receiver operating characteristic curve was 0.94 (95% CI, 0.92–0.96). Conclusion: This meta-analysis suggests IL-6 has a high diagnostic value for the differentiation of bacterial infection in patients with cirrhosis.